The Dragon and the Elephant - David Smith (Profile Books, 2007)
By 2050 the world's three biggest economies will be China, the US and India, respectively. Smith analyses the ways in which the world is tilting rapidly eastwards, and examines the implications of the shift in global power to Beijing and Delhi.